Method for producing latex composition

By controlling the pH value in the latex combination aging step and using sulfide-based vulcanizing agent and aroma compound, the allergic problems and insufficient mechanical properties of the dip mold during use are solved, and high stability and excellent mechanical properties are achieved.

JP7655304B2Active Publication Date: 2025-04-02ZEON CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022501816
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-20
Filing Date
2021-02-08
Publication Date
2025-04-02
Estimated Expiration
2041-02-08

AI Technical Summary

Technical Problem

When used, the existing latex combination dip molds are prone to cause immediate allergies (Type I) and delayed allergies (Type IV) when users are exposed, and the tension strength, tensile strength, tensile strength and tear strength of the mold are insufficient without using sulfide catalysts.

Method used

By controlling the pH value at 9 or above in the aging step of the latex combination, and storing it for maturation between 12 hours and 14 days, a sulfide-based vulcanizing agent and scented compounds are used, and strong acidic surfactants are added if necessary to improve the stability and mechanical properties of the latex combination.

Benefits of technology

The high stability and excellent tension, tensile strength, tensile strength and tear strength of the latex combined dip mold are achieved, while avoiding the occurrence of delayed allergies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655304000001
    Figure 0007655304000001
Patent Text Reader

Abstract

Provided is a latex composition production method comprising: a preparation step for preparing a conjugated diene-based polymer latex, a processing step for adding a sulfur-based vulcanizing agent and a xanthogen compound to the conjugated diene-based polymer latex to obtain a pre-aging latex composition; and an aging step for, after the pre-aging latex composition is processed, aging the processed pre-aging latex composition by storing for 12 hours to 14 days in a 5-60°C temperature condition, wherein, in the aging step, the pH of the latex composition 12 hours after the start of the aging is 9 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a latex composition, and more particularly to a method for producing a dip-molded article using the latex composition obtained by such a production method, which can provide a film-molded article such as a dip-molded article having excellent stability and excellent tensile strength, tensile elongation, and tear strength. [Background technology]

[0002] It has been known that latex compositions containing natural rubber latex are dip molded to obtain film-formed articles such as dip molded articles that are used in contact with the human body, such as nipples, balloons, gloves, balloons, and sacks. However, natural rubber latex contains proteins that cause symptoms of immediate-type allergy (Type I) in the human body, and therefore may be problematic as a dip molded article that comes into direct contact with the mucous membranes or organs of the body. For this reason, studies have been made on removing proteins in natural rubber latex by purification or the like, or on using synthetic rubber latex instead of natural rubber.

[0003] For example, Patent Document 1 discloses a latex composition for dip molding, which is obtained by compounding zinc oxide, sulfur, and a vulcanization accelerator with a latex of synthetic polyisoprene, which is a synthetic rubber. However, while the technology of Patent Document 1 can prevent the occurrence of immediate-type allergy (Type I) caused by proteins derived from natural rubber, when the dip molded product is made into a dip molded product, the vulcanization accelerator contained in the dip molded product may cause allergic symptoms of delayed-type allergy (Type IV) when the product comes into contact with the human body. When a vulcanization accelerator that causes symptoms of delayed-type allergy (Type IV) is not compounded, the obtained dip molded product does not have sufficient tensile strength, tensile elongation, and tear strength. Therefore, there has been a demand for improvement in the tensile strength, tensile elongation, and tear strength of a dip molded product when a vulcanization accelerator that causes symptoms of delayed-type allergy (Type IV) is not compounded. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2014 / 129547 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing a latex composition which can provide a film-formed product such as a dip-molded product having excellent stability, and excellent tensile strength, tensile elongation, and tear strength, and a method for producing a dip-molded product using the latex composition obtained by such a production method. [Means for solving the problem]

[0006] As a result of intensive investigations to achieve the above object, the present inventors have found that the above object can be achieved by adjusting the pH 12 hours after the start of aging in a specific range in an aging step carried out after preparation of a latex composition, and have thus completed the present invention.

[0007] That is, according to the present invention, there is provided a method for producing a latex composition, comprising: a preparation step of preparing a conjugated diene polymer latex; a preparation step of adding a sulfur-based vulcanizing agent and a xanthogen compound to the conjugated diene polymer latex to obtain a pre-ripened latex composition; and an aging step of storing the pre-ripened latex composition at a temperature of 5 to 60°C for 12 hours to 14 days to age the composition, in which the pH of the latex composition 12 hours after the start of aging in the aging step is set to 9 or more.

[0008] In the method for producing a latex composition of the present invention, it is preferable that the pH of the latex composition before aging is adjusted to 11 or more in the preparation step. In the method for producing a latex composition of the present invention, it is preferable to add a pH adjuster to the latex composition during maturation in the maturation step. In the method for producing a latex composition of the present invention, the pH adjuster preferably contains at least one selected from the group consisting of an alkali metal hydroxide, ammonia, and an organic amine compound. In the method for producing a latex composition of the present invention, the amount of the sulfur-based vulcanizing agent used is preferably 0.01 to 3 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex. In the method for producing a latex composition of the present invention, the amount of the xanthogen compound used is preferably 0.01 to 10 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex. In the method for producing a latex composition of the present invention, it is preferable that a strong acid salt surfactant is further added to the conjugated diene polymer latex in the preparation step. In the method for producing a latex composition of the present invention, the conjugated diene polymer latex is preferably a synthetic polyisoprene latex, a styrene-isoprene-styrene block copolymer latex, or a deproteinized natural rubber latex. In the method for producing a latex composition of the present invention, the conjugated diene polymer latex is preferably a latex of a conjugated diene polymer having no carboxyl group.

[0009] According to the present invention, there is also provided a method for producing a dip-molded article, comprising a step of dip-molding the latex composition obtained by the above-mentioned production method. Effect of the Invention

[0010] According to the present invention, there can be provided a method for producing a latex composition which can give a film-formed article such as a dip-molded article having excellent stability and excellent tensile strength, tensile elongation, and tear strength, and a method for producing a dip-molded article using the latex composition obtained by such a production method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The method for producing a latex composition of the present invention includes a preparation step of preparing a conjugated diene polymer latex, a preparation step of adding a sulfur-based vulcanizing agent and a xanthogen compound to the conjugated diene polymer latex to obtain a pre-ripening latex composition; and an aging step of preparing the pre-aged latex composition and then storing the prepared pre-aged latex composition at a temperature of 5 to 60° C. for 12 hours to 14 days to age the composition, In the aging step, the pH of the latex composition 12 hours after the start of aging is adjusted to 9 or more.

[0012] The preparation step of the present invention is a step of preparing a conjugated diene polymer latex to be used in the preparation step described below. The conjugated diene polymer latex used in the present invention is not particularly limited as long as it is a latex in which a conjugated diene polymer is dispersed in water.

[0013] <Conjugated diene polymer latex> The conjugated diene polymer latex used in the present invention is not particularly limited, but may be, for example, synthetic polyisoprene latex, styrene-isoprene-styrene block copolymer (SIS) latex, protein-removed natural rubber (deproteinized natural rubber) latex, or nitrile group-containing conjugated diene copolymer latex. Among these, synthetic polyisoprene latex, SIS latex, deproteinized natural rubber latex, or other polymer latexes containing isoprene units are preferred, and synthetic polyisoprene latex is particularly preferred. The conjugated diene polymer latex used in the present invention may have a modified group such as a carboxyl group, but from the viewpoint of reducing the number of manufacturing steps, it is preferred to use a conjugated diene polymer latex that does not have a carboxyl group. The conjugated diene polymer having no carboxyl group may be any conjugated diene polymer having substantially no carboxyl group, and may contain, for example, a carboxyl group in an amount attributable to impurities or the like (for example, an amount of less than about 0.05% by weight calculated as a monomer unit).

[0014] When synthetic polyisoprene latex is used as the conjugated diene polymer latex, the synthetic polyisoprene contained in the synthetic polyisoprene latex may be a homopolymer of isoprene or may be a copolymer of isoprene and other ethylenically unsaturated monomers copolymerizable therewith. The content of isoprene units in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) based on the total monomer units, since it is easy to obtain a membrane molded product such as a dip molded product that is flexible and has excellent tensile strength.

[0015] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene, such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers, such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers, such as styrene and alkylstyrene; ethylenically unsaturated carboxylate monomers, such as methyl (meth)acrylate (meaning "methyl acrylate and / or methyl methacrylate", hereinafter the same applies to ethyl (meth)acrylate, etc.), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and the like. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination.

[0016] Synthetic polyisoprene can be obtained by a conventionally known method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers used as necessary in an inert polymerization solvent using a Ziegler-based polymerization catalyst consisting of trialkylaluminum-titanium tetrachloride or an alkyl lithium polymerization catalyst such as n-butyl lithium or sec-butyl lithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization may be used as it is for the production of synthetic polyisoprene latex, but solid synthetic polyisoprene can also be taken out of the polymer solution and then dissolved in an organic solvent for use in the production of synthetic polyisoprene latex. When the synthetic polyisoprene polymer solution is obtained by the above-mentioned method, impurities such as the residue of the polymerization catalyst remaining in the polymer solution may be removed. In addition, an antioxidant described later may be added to the solution during or after the polymerization. In addition, commercially available solid synthetic polyisoprene may be used.

[0017] There are four types of isoprene units in synthetic polyisoprene, depending on the bonding state of isoprene: cis bond unit, trans bond unit, 1,2-vinyl bond unit, and 3,4-vinyl bond unit. From the viewpoint of improving the tensile strength of the obtained film molded article such as a dip molded article, the content of cis bond units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, based on the total isoprene units.

[0018] The weight-average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, as calculated based on standard polystyrene by gel permeation chromatography analysis. By setting the weight-average molecular weight of the synthetic polyisoprene within the above range, the tensile strength, tensile elongation, and tear strength of a film-formed product such as a dip-formed product are further improved, and the synthetic polyisoprene latex tends to be easily produced.

[0019] In addition, the polymer Mooney viscosity (ML 1+4 , 100° C.) is preferably 50 to 80, more preferably 60 to 80, and further preferably 70 to 80.

[0020] Methods for obtaining synthetic polyisoprene latex include, for example, (1) a method in which a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce a synthetic polyisoprene latex, and (2) a method in which isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith is emulsion polymerized or suspension polymerized in the presence of an emulsifier to directly produce a synthetic polyisoprene latex. Among these, the above-mentioned production method (1) is preferred in that it can use synthetic polyisoprene having a high ratio of cis-bond units in the isoprene units and can easily produce a film molded product such as a dip molded product having excellent mechanical properties such as tensile strength.

[0021] Examples of the organic solvent used in the above production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, cyclohexene, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; halogenated hydrocarbon solvents such as methylene chloride, chloroform, ethylene dichloride, etc. Among these, alicyclic hydrocarbon solvents and aliphatic hydrocarbon solvents are preferred, pentane, cyclohexane, and n-hexane are more preferred, and n-hexane is particularly preferred.

[0022] The amount of the organic solvent used is preferably 2,000 parts by weight or less, more preferably 20 to 1,500 parts by weight, and even more preferably 500 to 1,500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.

[0023] As the emulsifier used in the above production method (1), it is preferable to use an ionic emulsifier, and among these, it is more preferable to use an anionic emulsifier. Examples of the anionic emulsifier include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, sodium rosinate, and potassium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkyl sulfate salts such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; and monoalkyl phosphate salts such as sodium lauryl phosphate and potassium lauryl phosphate.

[0024] Among these anionic emulsifiers, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfates and polyoxyethylene alkyl ether sulfates are preferred, with fatty acid salts and alkylbenzenesulfonates being particularly preferred.

[0025] In addition, since the polymerization catalyst (particularly aluminum and titanium) remaining in trace amounts derived from synthetic polyisoprene can be more efficiently removed and the generation of aggregates during the production of a latex composition can be suppressed, at least one selected from the group consisting of alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt can be used in combination with a fatty acid salt. Here, sodium rosinate and potassium rosinate are preferred as the fatty acid salt, and sodium dodecylbenzenesulfonate and potassium dodecylbenzenesulfonate are preferred as the alkylbenzenesulfonate. These emulsifiers may be used alone or in combination of two or more.

[0026] As described above, by using at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates in combination with a fatty acid salt, the obtained latex contains at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates, and a fatty acid salt.

[0027] Examples of ionic emulsifiers other than anionic emulsifiers include copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers.

[0028] Furthermore, nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters may also be used in combination, so long as they do not inhibit coagulation by the coagulant used in dip molding.

[0029] The amount of the emulsifier used in the above production method (1) is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and even more preferably 5 to 15 parts by weight, relative to 100 parts by weight of synthetic polyisoprene. When two or more kinds of emulsifiers are used, it is preferable that the total amount of these is within the above range. That is, for example, when at least one selected from alkylbenzene sulfonate, alkyl sulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt is used in combination with a fatty acid salt, it is preferable that the total amount of these is within the above range. By setting the amount of the emulsifier to the above range, the generation of aggregates during emulsification can be further suppressed.

[0030] In addition, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is used in combination with a fatty acid salt as an anionic emulsifier, the weight ratio of the "fatty acid salt" to the "total of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate" is preferably in the range of 1:1 to 10:1, more preferably in the range of 1:1 to 7:1. By setting the weight ratio of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate in the above range, foaming that occurs when handling synthetic polyisoprene can be suppressed, which eliminates the need for operations such as leaving the mixture for a long time or adding an antifoaming agent, leading to improved workability and reduced costs.

[0031] The amount of water used in the above production method (1) is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of synthetic polyisoprene. The type of water used may be hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc., with soft water, ion-exchanged water, and distilled water being preferred.

[0032] The device for emulsifying the solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier is not particularly limited, and can be any device that is commercially available as an emulsifier or disperser. The method for adding the emulsifier to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and the emulsifier may be added in advance to either water or the solution or fine suspension of synthetic polyisoprene, or to both, or may be added to the emulsion during the emulsification operation, or may be added all at once or in portions.

[0033] Examples of emulsifying devices include batch emulsifying machines such as "Homogenizer" (manufactured by IKA), "Polytron" (manufactured by Kinematica), and "TK Auto Homo Mixer" (manufactured by Tokushu Kika Kogyo); "TK Pipeline Homo Mixer" (manufactured by Tokushu Kika Kogyo), "Colloid Mill" (manufactured by Kobe Steel Pantech), "Thrasher" (manufactured by Nippon Coke & Engineering Co., Ltd.), "Trigonal Wet Fine Grinding Mill" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), "Cavitron" (manufactured by Eurotech), and Examples of such machines include continuous emulsifiers such as "Milder" (manufactured by Pacific Machinery & Engineering Co., Ltd.) and "Fine Flow Mill" (manufactured by Pacific Machinery & Engineering Co., Ltd.); high-pressure emulsifiers such as "Microfluidizer" (manufactured by Mizuho Kogyo Co., Ltd.), "Nanomizer" (manufactured by Nanomizer Co., Ltd.), and "APV Gaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as "Membrane Emulsifier" (manufactured by Reika Kogyo Co., Ltd.); vibration emulsifiers such as "Vibro Mixer" (manufactured by Reika Kogyo Co., Ltd.); and ultrasonic emulsifiers such as "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). The conditions for the emulsification operation using an emulsification device are not particularly limited, and the processing temperature, processing time, and the like may be appropriately selected so as to achieve the desired dispersion state.

[0034] In the above production method (1), it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation. As a method for removing the organic solvent from the emulsion, a method capable of reducing the content of the organic solvent (preferably an alicyclic hydrocarbon solvent or an aliphatic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less is preferable, and for example, a method such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted. The organic solvent can be removed while adding the defoaming agent, which can suppress foaming of the synthetic polyisoprene.

[0035] Furthermore, after removing the organic solvent, in order to increase the solid content concentration of the synthetic polyisoprene latex, a concentration operation may be carried out by a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration, etc., as necessary. In particular, from the viewpoint of increasing the solid content concentration of the synthetic polyisoprene latex and reducing the residual amount of the emulsifier in the synthetic polyisoprene latex, it is preferable to carry out centrifugation.

[0036] The centrifugation is preferably carried out using a continuous centrifuge under the conditions of a centrifugal force of preferably 100 to 10,000 G, a solids concentration of the synthetic polyisoprene latex before centrifugation of preferably 2 to 15% by weight, a flow rate of the centrifuge of preferably 500 to 1700 kg / hr, and a back pressure (gauge pressure) of the centrifuge of preferably 0.03 to 1.6 MPa, and a synthetic polyisoprene latex can be obtained as a light liquid after centrifugation. This can reduce the amount of emulsifier remaining in the synthetic polyisoprene latex.

[0037] The solid content of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By setting the solid content to the lower limit or higher of the above range, a film molded product such as a dip molded product described below is less likely to break. In addition, by setting the solid content to the upper limit or lower of the above range, the viscosity of the synthetic polyisoprene latex is prevented from becoming too high, and transportation through piping and stirring in a mixing tank are facilitated.

[0038] The volume average particle diameter of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter within the above range, the latex viscosity becomes appropriate and easy to handle, and also the formation of a film on the surface of the latex during storage of the synthetic polyisoprene latex can be suppressed.

[0039] The synthetic polyisoprene latex may further contain additives that are commonly used in the field of latex, such as a pH adjuster, an antifoaming agent, a preservative, a crosslinking agent, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.

[0040] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, alkali metal bicarbonates such as sodium bicarbonate, ammonia, and organic amine compounds such as trimethylamine and triethanolamine, with alkali metal hydroxides and ammonia being preferred. The pH of the synthetic polyisoprene latex in the preparation step is not particularly limited, but as described below, when a latex composition is prepared using the synthetic polyisoprene latex or the like and the latex composition is aged under predetermined conditions, it is preferred that the pH of the latex composition before aging is 10 or higher.

[0041] As the conjugated diene polymer latex, a latex of a styrene-isoprene-styrene block copolymer (SIS) can be used as described above. In SIS, "S" represents a styrene block, and "I" represents an isoprene block.

[0042] The SIS contained in the SIS latex can be obtained by a conventional method, for example, block copolymerization of isoprene and styrene in an inert polymerization solvent using an active organic metal such as n-butyl lithium as an initiator. The obtained SIS polymer solution can be used as it is for the production of the SIS latex, but the solid SIS can also be taken out of the polymer solution, and then dissolved in an organic solvent to be used for the production of the SIS latex. The method for producing the SIS latex is not particularly limited, but a method in which a solution or fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce the SIS latex is preferred. In this case, impurities such as the residue of the polymerization catalyst remaining in the polymer solution after synthesis may be removed. In addition, an antioxidant, which will be described later, may be added to the solution during or after polymerization. Commercially available solid SIS may also be used.

[0043] As the organic solvent, the same ones as in the case of the synthetic polyisoprene can be used, and aromatic hydrocarbon solvents and alicyclic hydrocarbon solvents are preferred, with cyclohexane and toluene being particularly preferred. The amount of the organic solvent used is usually 50 to 2,000 parts by weight, preferably 80 to 1,000 parts by weight, more preferably 10 to 500 parts by weight, and further preferably 150 to 300 parts by weight, based on 100 parts by weight of the SIS.

[0044] Examples of the emulsifier include the same ones as those in the case of the synthetic polyisoprene, and anionic emulsifiers are preferred, with potassium rosinate and sodium dodecylbenzenesulfonate being particularly preferred.

[0045] The amount of the emulsifier used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and further preferably 5 to 15 parts by weight, based on 100 parts by weight of the SIS. By setting the amount of the emulsifier used within the above range, the stability of the obtained latex can be improved.

[0046] The amount of water used in the above-mentioned SIS latex production method is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, based on 100 parts by weight of the SIS organic solvent solution. The type of water used may include hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc. Also, a polar solvent, typified by an alcohol such as methanol, may be used in combination with water.

[0047] The apparatus for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of an emulsifier can be the same as that for the synthetic polyisoprene. The method of adding the emulsifier is not particularly limited, and it may be added in advance to either the water or the organic solvent solution or fine suspension of SIS, or to both, or it may be added to the emulsion during the emulsification operation, or it may be added all at once or in portions.

[0048] In the above-mentioned method for producing SIS latex, it is preferable to obtain SIS latex by removing the organic solvent from the emulsion obtained through the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited, and methods such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted. The organic solvent can be removed while adding the defoaming agent. The addition of the defoaming agent can suppress foaming.

[0049] After removing the organic solvent, the SIS latex may be concentrated by vacuum distillation, atmospheric distillation, centrifugation, membrane concentration or the like, if necessary, in order to increase the solids concentration of the SIS latex.

[0050] The solid content of the SIS latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content at or above the lower limit of the above range, a film molded product such as a dip molded product described below is less likely to break. In addition, by making the solid content at or below the upper limit of the above range, the viscosity of the SIS latex is prevented from becoming too high, and it becomes easy to transport it through piping or to stir it in a mixing tank.

[0051] In addition, the SIS latex may contain additives such as pH adjusters, antifoamers, preservatives, crosslinking agents, chelating agents, oxygen scavengers, dispersants, and antioxidants, which are generally used in the field of latex. Examples of pH adjusters include the same ones as those in the case of the synthetic polyisoprene, and alkali metal hydroxides or ammonia are preferred. The pH of the SIS latex in the preparation step is not particularly limited, but as described below, when a latex composition is made using the SIS latex or the like and the latex composition is aged under a specified condition, it is preferred that the pH of the latex composition before aging is 10 or more.

[0052] The content of styrene units in the styrene block in the SIS contained in the SIS latex thus obtained is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content of isoprene units in the isoprene block in the SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content ratio of styrene units and isoprene units in SIS, in terms of the weight ratio of "styrene units:isoprene units", is usually in the range of 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and further preferably 10:90 to 30:70.

[0053] The weight-average molecular weight of the SIS, calculated as standard polystyrene by gel permeation chromatography analysis, is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000. By setting the weight-average molecular weight of the SIS within the above range, the balance between the tensile strength and flexibility of a film-formed product such as a dip-formed product is improved, and the production of a SIS latex tends to be easier.

[0054] The volume average particle diameter of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter of the latex particles within the above range, the viscosity of the latex becomes appropriate, making it easy to handle, and also preventing a film from being formed on the surface of the latex during storage of the SIS latex.

[0055] As the conjugated diene polymer latex, a latex of a nitrile group-containing conjugated diene copolymer can also be used, as described above.

[0056] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer with an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to the above, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0057] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and even more preferably 56 to 68% by weight. By setting the content of the conjugated diene monomer unit within the above range, the obtained film molded product such as a dip molded product can be made to have sufficient tensile strength and excellent texture and elongation.

[0058] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer unit formed by the ethylenically unsaturated nitrile monomer in the nitrile group-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and even more preferably 30 to 40% by weight. By setting the content of the ethylenically unsaturated nitrile monomer unit within the above range, the obtained film molded product such as a dip molded product can be made to have sufficient tensile strength while being excellent in texture and elongation.

[0059] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include vinyl aromatic monomers such as styrene, alkylstyrene, and vinylnaphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, dibutyl fumarate, diethyl maleate, (meth)acrylamide, ethyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, dibutyl fumarate, diethyl maleate, (meth)acrylamide, ethyl methacrylate ... Examples of the ethylenically unsaturated carboxylic acid ester monomers include methoxymethyl acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; crosslinkable monomers include divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate; and the like. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0060] In the nitrile group-containing conjugated diene copolymer, the content of other monomer units formed by other ethylenically unsaturated monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.

[0061] The nitrile group-containing conjugated diene copolymer can be obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, and a method of copolymerizing by emulsion polymerization is preferred. As the emulsion polymerization method, a conventionally known method can be adopted.

[0062] When the monomer mixture containing the above-mentioned monomers is emulsion-polymerized, it is possible to use commonly used polymerization auxiliary materials such as an emulsifier, a polymerization initiator, a molecular weight regulator, etc. The method of adding these polymerization auxiliary materials is not particularly limited, and any method such as initial lump-sum addition, divided addition, or continuous addition may be used.

[0063] The emulsifier is not particularly limited, but examples thereof include nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, and polyoxyethylene sorbitan alkyl ester; anionic emulsifiers such as alkylbenzene sulfonate salts such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate salts, and alkyl sulfosuccinate salts; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzylammonium chloride; and copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Among these, anionic emulsifiers are preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of emulsifier used is preferably 0.1 to 10 parts by weight based on 100 parts by weight of the monomer mixture.

[0064] The polymerization initiator is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more kinds. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 2 parts by weight, based on 100 parts by weight of the monomer mixture.

[0065] The peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but includes compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; and amine compounds such as dimethylaniline. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight per 100 parts by weight of the peroxide.

[0066] The amount of water used in emulsion polymerization is preferably from 80 to 600 parts by weight, particularly preferably from 100 to 200 parts by weight, based on 100 parts by weight of the total monomers used.

[0067] Examples of the method of adding the monomers include a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then polymerizing by adding the remaining monomers continuously or intermittently, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, the various monomers to be used may be mixed in advance and then added to the reaction vessel, or each monomer may be added to the reaction vessel separately.

[0068] Furthermore, if necessary, polymerization auxiliary materials such as a chelating agent, a dispersing agent, a pH adjuster, an oxygen scavenger, and a particle size adjuster can be used, and the type and the amount of these are not particularly limited.

[0069] The polymerization temperature when carrying out the emulsion polymerization is not particularly limited, but is usually 3 to 95° C., and preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0070] As described above, the monomer mixture is emulsion-polymerized, and when a predetermined polymerization conversion rate is reached, the polymerization reaction is terminated by cooling the polymerization system or adding a polymerization terminator. The polymerization conversion rate at the time of terminating the polymerization reaction is preferably 90% by weight or more, more preferably 93% by weight or more.

[0071] The polymerization terminator is not particularly limited, but examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzenedithiocarboxylic acid, and hydroxydibutylbenzenedithiocarboxylic acid and their alkali metal salts, and alcohols such as methanol, ethanol, and isopropanol. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight based on 100 parts by weight of the monomer mixture.

[0072] After the polymerization reaction is terminated, if desired, unreacted monomers are removed and the solid content and pH are adjusted to obtain a latex of a nitrile group-containing conjugated diene copolymer.

[0073] Furthermore, to the latex of the nitrile group-containing conjugated diene copolymer, an antioxidant, a preservative, an antibacterial agent, a dispersant, etc. may be appropriately added, if necessary.

[0074] The number average particle size of the latex of the nitrile group-containing conjugated diene copolymer is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by, for example, adjusting the amounts of the emulsifier and polymerization initiator used.

[0075] As the conjugated diene polymer latex, a latex of natural rubber from which proteins have been removed (deproteinized natural rubber) can also be used as the conjugated diene polymer latex, as described above. As the deproteinized natural rubber latex, there can be used what is known as "deproteinized natural rubber latex", which is obtained by a known protein removal method, such as a method in which proteins in natural rubber latex are decomposed with a protease or a surfactant, and then removed by washing or centrifugation.

[0076] As described above, the conjugated diene polymer used in the present invention may be synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), nitrile group-containing conjugated diene copolymer, deproteinized natural rubber, or the like. However, the present invention is not limited to these, and may also use butadiene polymer, styrene-butadiene copolymer, or the like.

[0077] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer with another ethylenically unsaturated monomer that is copolymerizable with the conjugated diene monomer.

[0078] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing styrene with 1,3-butadiene as a conjugated diene monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0079] The conjugated diene polymer latex used in the present invention may contain additives that are commonly used in the field of latexes, such as a pH adjuster, an antifoaming agent, a preservative, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.

[0080] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, alkali metal hydrogen carbonates such as sodium hydrogen carbonate, ammonia, and organic amine compounds such as trimethylamine and triethanolamine, with alkali metal hydroxides and ammonia being preferred. The pH of the conjugated diene polymer latex in the preparation step is not particularly limited, but in the production method of the present invention, as described below, when a xanthogen compound and a sulfur-based vulcanizing agent are blended with the conjugated diene polymer latex to prepare a latex composition, and the latex composition is aged under predetermined conditions, the pH of the latex composition 12 hours after the start of aging should be 9 or more.

[0081] In addition, if necessary, in order to increase the solid content concentration of the conjugated diene polymer latex, a concentration operation may be performed by a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration, etc., but from the viewpoint of being able to adjust the residual amount of emulsifier in the conjugated diene polymer latex, it is preferable to perform centrifugation.

[0082] When subjecting the conjugated diene polymer latex to a centrifuge, in order to improve the mechanical stability of the latex, it is preferable to add a pH adjuster in advance to adjust the pH of the latex to 7 or more, more preferably to adjust the pH to 9 or more.

[0083] The solid content of the conjugated diene polymer latex used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By setting the solid content within the above range, the generation of aggregates in the latex can be more effectively suppressed, and the separation of polymer particles during storage of the latex can be more effectively suppressed.

[0084] <Preparation process> In the production method of the present invention, a sulfur-based vulcanizing agent and a xanthogen compound are added to the above-mentioned conjugated diene polymer latex to prepare a latex composition containing them (preparation step).

[0085] The sulfur-based vulcanizing agent is not particularly limited, but examples thereof include powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-dithio-bis(hexahydro-2H-azepinone-2)), phosphorus-containing polysulfide, polymer polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.

[0086] The amount of the sulfur-based vulcanizing agent used is not particularly limited, but is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 3 parts by weight, even more preferably 0.1 to 3 parts by weight, even more preferably 0.2 to 3 parts by weight, and particularly preferably 1 to 2 parts by weight, based on 100 parts by weight of the conjugated diene polymer contained in the latex composition. By setting the content of the sulfur-based vulcanizing agent within the above range, the tensile strength of the obtained film molded product such as a dip molded product can be further increased while suppressing the occurrence of delayed-type allergy (Type IV) symptoms.

[0087] The xanthogen compound used in the present invention acts as a vulcanization accelerator when used in combination with a sulfur-based vulcanizing agent. That is, when a sulfur-based vulcanizing agent is blended into a latex composition and a conjugated diene polymer in the latex composition is vulcanized with the sulfur-based vulcanizing agent to form a film-formed body such as a dip-molded body, the xanthogen compound acts as a vulcanization accelerator. The xanthogen compound acts as a vulcanization accelerator in the latex composition blended with the sulfur-based vulcanizing agent, and after vulcanization, is decomposed into alcohol, carbon disulfide, etc. by heat applied during vulcanization. For example, the xanthogen compound is decomposed into alcohol, carbon disulfide, etc. by heat applied during production of a film-formed body (heat of about 100 to 130°C during vulcanization of a conjugated diene polymer), and further, the components generated by the decomposition (alcohol, carbon disulfide, etc.) volatilize. As a result, the film-formed body obtained has a reduced amount of residual xanthogen compound. That is, in the method for producing the latex composition of the present invention, a xanthogen compound is used as a vulcanization accelerator without using a vulcanization accelerator (e.g., dithiocarbamate vulcanization accelerator, thiazole vulcanization accelerator, etc.) which has been a cause of delayed-type allergy (Type IV) symptoms in the past. This makes it possible to reduce the amount of the xanthogen compound remaining in the obtained film molded product such as a dip-molded product, and therefore makes it possible to suppress the occurrence of delayed-type allergy (Type IV) symptoms in the obtained film molded product.

[0088] The xanthogen compound used in the present invention is not particularly limited, but examples thereof include xanthogenic acid, xanthogen salts, xanthogen disulfide (a compound in which two xanthogenic acids are bonded via a sulfur atom or the like), and xanthogen polysulfide (a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like).

[0089] The xanthogenate may be any salt having a xanthogenic acid structure, and is not particularly limited thereto. For example, the xanthogenate may be a compound represented by the general formula (ROC(=S)S)xZ (wherein R is a linear or branched hydrocarbon, Z is a metal atom, and x is a number matching the valence of Z, and is usually 1 to 4, preferably 2 to 4, and particularly preferably 2).

[0090] The xanthogenate represented by the above general formula (ROC(=S)S)xZ is not particularly limited, and examples thereof include zinc dimethylxanthogenate, zinc diethylxanthogenate, zinc dipropylxanthogenate, zinc diisopropylxanthogenate, zinc dibutylxanthogenate, zinc dipentylxanthogenate, zinc dihexylxanthogenate, zinc diheptylxanthogenate, zinc dioctylxanthogenate, zinc di(2-ethylhexyl)xanthogenate, zinc didecylxanthogenate, zinc didodecylxanthogenate, potassium dimethylxanthogenate, potassium ethylxanthogenate, potassium propylxanthogenate, potassium isopropylxanthogenate, potassium butylxanthogenate, and potassium pentylxanthogenate. Examples of suitable xanthates include potassium xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium pentyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, and sodium dodecyl xanthogenate. Among these, xanthogenates in which x in the above general formula (ROC(=S)S)xZ is 2 or more are preferred, isopropyl xanthogenates and butyl xanthogenates are more preferred, and zinc diisopropyl xanthogenate and zinc dibutyl xanthogenate are particularly preferred. These xanthogenates may be used alone or in combination.

[0091] Xanthogen disulfide is a compound in which two xanthogenic acids are bonded via a sulfur atom or the like, and examples of such compounds include, but are not limited to, dimethylxanthogen disulfide, diethylxanthogen disulfide, diisopropylxanthogen disulfide, dibutylxanthogen disulfide, dimethylxanthogen polysulfide, diethylxanthogen polysulfide, diisopropylxanthogen polysulfide, and dibutylxanthogen polysulfide. Of these, diisopropylxanthogen disulfide and dibutylxanthogen disulfide are preferred.

[0092] Xanthogen polysulfides are compounds in which three or more xanthogenic acids are bonded together via sulfur atoms, etc., and examples include xanthogen trisulfide, in which three xanthogenic acids are bonded together via sulfur, xanthogen tetrasulfide, in which four xanthogenic acids are bonded together via sulfur, and xanthogen pentasulfide, in which five xanthogenic acids are bonded together via sulfur.

[0093] The latex composition may contain one kind of xanthogen compound alone, but preferably contains two or more kinds of xanthogen compounds. For example, when xanthogen acid is blended into the latex composition, a part of the blended xanthogen acid may exist in the form of a xanthogen salt, so that the latex composition contains two or more kinds of xanthogen compounds. Alternatively, a part of the xanthogen acid blended into the latex composition may exist in the form of a xanthogen disulfide or a xanthogen polysulfide due to the action of a sulfur-based vulcanizing agent in the latex composition. Similarly, when a xanthogen salt, a xanthogen disulfide, or a xanthogen polysulfide is blended into the latex composition, each of them may exist in the form of a xanthogen acid, a xanthogen salt, a xanthogen disulfide, or a xanthogen polysulfide.

[0094] The amount of the xanthogen compound used (when a plurality of xanthogen compounds are contained, the total amount used) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, even more preferably 0.5 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer contained in the latex. By setting the amount of the xanthogen compound used within the above range, the tensile strength of the obtained film molded article such as a dip molded article can be further improved while suppressing the occurrence of delayed-type allergy (Type IV) symptoms.

[0095] In the present invention, it is preferable that the latex composition does not substantially contain any compound that has been conventionally used as a vulcanization accelerator, specifically, a vulcanization accelerator containing sulfur that causes the occurrence of delayed type allergy (Type IV) symptoms (e.g., dithiocarbamate vulcanization accelerator, thiazole vulcanization accelerator, etc.), other than the xanthogen compound, and that remains in a film molded product such as a dip molded product obtained after acting as a vulcanization accelerator.

[0096] In the production method of the present invention, a strong acid salt surfactant may be added to the above-mentioned conjugated diene polymer latex, if necessary, in addition to the sulfur-based vulcanizing agent and the xanthogen compound.

[0097] The strong acid salt surfactant is not particularly limited as long as it has a structure derived from a salt of a strong acid and a strong base and has a surface active effect, but for example, it can be a compound having a sulfonate group, a compound having a sulfate group or a sulfate ester group, a compound having a phosphate group or a phosphate ester group, a compound having a nitrate group, etc., and among these, a compound having a sulfonate group, a compound having a phosphate group or a phosphate ester group is preferred. Note that these strong acid salt surfactants can be used alone or in combination of two or more types.

[0098] The compound having a sulfonate group as the strong acid salt surfactant is not particularly limited as long as it is a compound having a salt structure in which a sulfo group is neutralized with a strong base, and examples thereof include sodium salt of β-naphthalenesulfonic acid formalin condensate (NASF), sodium alkylbenzenesulfonate, sodium 1-hexanesulfonate, and trisodium naphthalenetrisulfonate.

[0099] The compound having a sulfate group or a sulfate ester group as the strong acid salt surfactant is not particularly limited as long as it is a compound having a salt structure in which the sulfate group or the sulfate ester group is neutralized with a strong base, and examples thereof include sodium lauryl sulfate.

[0100] The compound having a phosphate group or a phosphate ester group as the strong acid salt surfactant is not particularly limited as long as it is a compound having a salt structure in which the phosphate group or the phosphate ester group is neutralized with a strong base, and examples thereof include sodium lauryl phosphate and potassium lauryl phosphate.

[0101] The strong acid salt surfactant may also be a compound having a polycyclic structure. The polycyclic structure is not particularly limited as long as it has two or more ring structures, and examples thereof include a biphenyl structure in which two benzene rings are connected by a single bond, and a condensed polycyclic structure in which two or more single rings are condensed (condensed rings). The rings constituting the polycyclic structure may be alicyclic or aromatic rings, or may contain heteroatoms. The number of rings is not particularly limited, but is preferably two or more rings, and the upper limit in practical terms is about 10 rings. Examples of the condensed polycyclic structure include a dicyclopentadiene structure, a naphthalene structure, a fluorene structure, an anthracene structure, a phenanthrene structure, a triphenylene structure, a pyrene structure, and an ovalene structure.

[0102] Examples of compounds having a polycyclic structure as strong acid salt surfactants include sodium β-naphthalenesulfonate formalin condensate (NASF), sodium naphthalenesulfonate, disodium naphthalene disulfonate, trisodium naphthalene trisulfonate, and sodium butylnaphthalenesulfonate. Of these, sodium β-naphthalenesulfonate formalin condensate (NASF), which is a compound having a sulfonate group and a polycyclic structure, is preferred.

[0103] The amount of the strong acid salt surfactant used is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, even more preferably 0.5 to 3 parts by weight, and even more preferably 0.8 to 1.5 parts by weight, based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex. By setting the amount of the strong acid salt surfactant used within the above range, the tensile strength, tensile elongation, and tear strength of the obtained film molded product such as a dip molded product can be further improved. In addition, when a strong acid salt surfactant is used as an emulsifier when preparing the conjugated diene polymer latex, the above-mentioned amount is the amount excluding the amount of the strong acid salt surfactant used as the emulsifier. That is, for example, in the case of using a conjugated diene polymer latex obtained by emulsifying a solution or fine suspension of a conjugated diene polymer in water in the presence of an emulsifier, removing the organic solvent as necessary, and adjusting the solid content concentration to 30 to 70% by weight (more preferably 40 to 70% by weight, and even more preferably 50 to 70% by weight) by concentration, it is preferable to set the amount of the strong acid salt surfactant used in the above range after removing the organic solvent and adjusting the solid content concentration to 30 to 70% by weight (more preferably 40 to 70% by weight, and even more preferably 50 to 70% by weight).

[0104] The method of adding the sulfur-based vulcanizing agent and the xanthogen compound to the above-mentioned conjugated diene polymer latex is not particularly limited, but the sulfur-based vulcanizing agent and the xanthogen compound may be added in this order, or they may be added simultaneously. In addition to the sulfur-based vulcanizing agent and the xanthogen compound, when a strong acid salt surfactant is further added to the conjugated diene polymer latex, the method of addition is not particularly limited, but the sulfur-based vulcanizing agent, the xanthogen compound, and the strong acid salt surfactant may be added in this order, or they may be added simultaneously. Alternatively, the strong acid salt surfactant may be added in advance, and then the sulfur-based vulcanizing agent and the xanthogen compound may be added in this order, or the xanthogen compound and the sulfur-based vulcanizing agent may be added in this order. Among them, it is preferable to adopt a method of adding the strong acid salt surfactant in advance and then adding the sulfur-based vulcanizing agent and the xanthogen compound, from the viewpoint of making the latex composition more stable even when the pH of the latex composition is lowered due to the addition of the xanthogen compound. In this case, the order of addition of the sulfur-based vulcanizing agent and the xanthogen compound is not particularly limited, and either may be added first, or they may be added simultaneously. In addition, the sulfur-based vulcanizing agent, the xanthogen compound, and the strong acid salt surfactant may be added in the form of an aqueous solution or aqueous dispersion.

[0105] In the production method of the present invention, an activator may be added to the above-mentioned conjugated diene polymer latex, if necessary, in addition to the sulfur-based vulcanizing agent and the xanthogen compound.

[0106] By blending an activator in the latex composition, when the conjugated diene polymer in the latex composition is vulcanized with a sulfur-based vulcanizing agent using the obtained latex composition to form a film molded article such as a dip-molded article, the activator acts as a vulcanization accelerator together with the above-mentioned xanthogen compound, thereby further improving the tear strength of the obtained film molded article such as a dip-molded article.

[0107] The activator is not particularly limited, but it is preferable to use a metal compound from the viewpoint of improving the tear strength of the film-formed body such as the dip-formed body obtained. The metal compound is not particularly limited, but for example, a metal oxide, a metal compound containing at least one carbon atom, etc. are included. The metal constituting the metal compound is not particularly limited, but a typical metal (at least one element selected from the group consisting of Group 1 elements, Group 2 elements, Group 12 elements, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, Group 17 elements, and Group 18 elements) is preferable, Group 2 elements, Group 12 elements, Group 13 elements, and Group 14 elements are more preferable, zinc, magnesium, calcium, aluminum, and lead are further preferable, zinc, magnesium, and calcium are particularly preferable, and zinc is most preferable. These metal compounds may be used alone or in combination.

[0108] The metal oxide is not particularly limited, but from the viewpoint of further improving the tear strength of the resulting film molded article such as a dip-molded article, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide, and aluminum oxide are preferred, and zinc oxide is more preferred.

[0109] As the metal compound containing at least one carbon atom, from the viewpoint of further improving the tear strength of the obtained film-formed article such as a dip-formed article, carbonates, hydrogencarbonates, hydroxides, and organometallic compounds are preferred, and carbonates, hydrogencarbonates, and organometallic compounds are more preferred. Among these, inorganic salts such as carbonates and hydrogencarbonates are particularly preferred from the viewpoint of excellent stability of the compound itself and easy availability.

[0110] The amount of the activator used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and further preferably 1 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer contained in the latex composition. By setting the amount of the activator used within the above range, the tear strength of the obtained film molded product such as a dip molded product can be further improved.

[0111] The method of blending the activator is not particularly limited as long as it is a method that ultimately results in a mixture of the conjugated diene polymer latex and the activator.

[0112] Furthermore, a vulcanization accelerator may be further added to the latex composition within a range capable of suppressing the occurrence of symptoms of delayed-type allergy (Type IV) in the obtained film-formed article such as a dip-formed article.

[0113] As the vulcanization accelerator, those usually used in dip molding can be used, for example, dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc, 2-mercaptobenzothiazole zinc salt ... Examples of the vulcanization accelerator include captothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholino dithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazyl mercaptomethyl)urea. The vulcanization accelerator can be used alone or in combination of two or more.

[0114] Furthermore, the latex composition may further contain additives such as antioxidants; dispersants; reinforcing agents such as carbon black, silica, and talc; fillers such as calcium carbonate and clay; ultraviolet absorbers; and plasticizers, as required.

[0115] Antioxidants include 2,6-di-4-methylphenol, 2,6-di-t-butylphenol, butyl hydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis(2,6-di-t-butylphenyl)propionate, butyl hydroxyanisole ... phenol-based antioxidants not containing sulfur atoms, such as 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; 2,2'-thiobis-(4-methyl-6-t-butylphenol), 4,4'-thiobis-(6-t-butyl-o-cresol), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-trimethyl-2-phenylpropanediol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; Thiobisphenol-based antioxidants such as (triazin-2-ylamino)phenol; phosphite ester-based antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; sulfur ester-based antioxidants such as dilauryl thiodipropionate; phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamido)-diphenyla amine-based antioxidants such as amine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butyraldehyde-aniline condensate, quinoline-based antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, hydroquinone-based antioxidants such as 2,5-di-(t-amyl)hydroquinone, etc. These antioxidants can be used alone or in combination of two or more.

[0116] The content of the antioxidant is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and further preferably 1 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer.

[0117] The method of mixing various compounding agents into the latex composition is not particularly limited, but for example, a method of obtaining a composition containing a conjugated diene polymer latex, a sulfur-based vulcanizing agent, and a xanthogen compound as described above, and then mixing the obtained composition with various compounding agents to be mixed as necessary using a dispersing machine such as a ball mill, kneader, or disperser, or a method of obtaining a composition containing a conjugated diene polymer latex and a strong acid salt surfactant, using the above dispersing machine to prepare an aqueous dispersion of compounding components other than the conjugated diene polymer latex and the strong acid salt surfactant, and then mixing the aqueous dispersion into a latex composition containing a conjugated diene polymer latex and a strong acid salt surfactant, etc. may be mentioned. In addition, at least a part of the various compounding agents may be mixed after aging as described below.

[0118] The solid content concentration of the latex composition of the present invention is preferably 10 to 60% by weight, and more preferably 10 to 55% by weight.

[0119] The pH of the latex composition before aging obtained in the preparation process of the present invention is preferably 10 or more, more preferably 11 or more, and even more preferably 12 or more. By setting the pH of the latex composition before aging within the above range, the stability of the latex composition after aging can be further improved. The upper limit of the pH of the latex composition before aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.

[0120] <Aging process> In the present invention, the latex composition thus prepared is subjected to aging (pre-crosslinking) by storing it at a temperature of 5 to 60° C. for 12 hours to 14 days.

[0121] The temperature for aging is 5 to 60° C., preferably 10 to 30° C., and more preferably 10 to 25° C. If the aging temperature is too low, the mechanical properties of the resulting film-formed article such as a dip-formed article become insufficient. On the other hand, if the aging temperature is too high, the tensile strength of the resulting film-formed article such as a dip-formed article decreases.

[0122] The maturing time depends on the maturing temperature, but is 12 hours to 14 days, preferably 12 hours to 10 days, and more preferably 12 hours to 7 days. If the maturing time is too short, the mechanical properties of the resulting film-formed article such as a dip-formed article become insufficient. On the other hand, if the maturing time is too long, the tensile strength of the resulting film-formed article such as a dip-formed article decreases.

[0123] In the present invention, in the aging step, the pH of the latex composition 12 hours after the start of aging is set to 9 or more, preferably 9.5 or more, and more preferably 10 or more. If the pH of the latex composition 12 hours after the start of aging is lower than the above range, the resulting latex composition will have poor stability. Although the pH of the latex composition tends to gradually decrease due to aging from the start of aging, it is preferable to continuously maintain the pH of the latex composition at 9 or more from the start of aging to the end of aging, and it is more preferable to continuously maintain the above pH.

[0124] Here, in the present invention, by incorporating a xanthogen compound together with a sulfur-based vulcanizing agent into the conjugated diene polymer latex, the occurrence of delayed-type allergy (Type IV) can be effectively suppressed since the xanthogen compound does not cause delayed-type allergy (Type IV). On the other hand, the present inventors have found that when a latex composition containing a xanthogen compound is aged (precrosslinked) and then used to manufacture a film-formed product such as a dip-formed product, the amount of aggregates in the latex composition increases, making dip-formation difficult. In particular, this problem tends to become more pronounced when a conjugated diene polymer not containing a carboxyl group is used as the conjugated diene polymer latex.

[0125] In response to this, the present inventors conducted intensive research and found that such a problem can be effectively solved by setting the pH of the latex composition 12 hours after the start of aging to 9 or more when aging the latex composition. In particular, the present inventors conducted research and found that when a xanthogen compound is added to a conjugated diene polymer latex, the pH of the resulting latex composition decreases when the latex composition is aged (precrosslinked). The decrease in pH during aging is a unique phenomenon observed when a xanthogen compound is added. Although not bound by a specific theory, it is believed that the decrease in pH during the aging process is caused in part by the decomposition of the xanthogen compound. This decrease in pH impairs the stability of the latex composition, and as a result, it is believed that the amount of aggregates in the latex composition increases. In response to this, the present invention found that the above problem can be solved by setting the pH of the latex composition 12 hours after the start of aging to 9 or more.

[0126] The method for adjusting the pH of the latex composition to 9 or more 12 hours after the start of aging is not particularly limited, but examples thereof include a method of adjusting the pH of the latex composition before aging to 11 or more in a preparation step, and a method of adding a pH adjuster to the latex composition during aging.

[0127] In the present invention, the pH of the latex composition 12 hours after the start of aging should be 9 or more, and the pH of the latex composition after aging is not particularly limited, but is preferably 9 or more, more preferably 9.5 or more, and even more preferably 10 or more. By setting the pH of the latex composition after aging in the above range, the stability of the obtained latex composition can be further improved. The upper limit of the pH of the latex composition after aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.

[0128] In the present invention, the pH may be adjusted to the above range by adding a pH adjuster to the latex composition after or during aging. The timing of adding the pH adjuster to the latex composition after or during aging is not particularly limited, but it is preferable to add it within 24 hours from the start of aging, more preferable to add it within 12 hours from the start of aging from the viewpoint of making the pH of the latex composition as high as possible 12 hours after the start of aging, and further preferable to add the pH adjuster within 1 hour from the start of aging considering that the pH of the latex composition tends to gradually decrease from the start of aging.

[0129] The pH adjuster to be added to the latex composition after or during aging is not particularly limited, but examples thereof include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, alkali metal hydrogen carbonates such as sodium hydrogen carbonate, ammonia, organic amine compounds such as trimethylamine and triethanolamine, etc., with alkali metal hydroxides, ammonia or organic amine compounds being preferred. These pH adjusters can be used alone or in combination of two or more.

[0130] According to the method for producing a latex composition of the present invention, the latex composition before aging, which contains a conjugated diene polymer latex, a sulfur-based vulcanizing agent, and a xanthogen compound, is aged to have a pH of 9 or more 12 hours after the start of aging. This makes it possible to make the latex composition itself excellent in stability, and also makes it possible to make the obtained film molded product such as a dip molded product excellent in tensile strength, tensile elongation, and tear strength while suppressing the occurrence of symptoms of delayed-type allergy (Type IV).

[0131] <Dip-molded body> In the method for producing a dip-molded article of the present invention, a dip-molded article can be obtained by dip-molding the latex composition obtained by the above-mentioned production method of the present invention. Dip molding is a method in which a mold is immersed in a latex composition, the composition is deposited on the surface of the mold, the mold is then removed from the composition, and the composition deposited on the surface of the mold is then dried. The mold may be preheated before being immersed in the latex composition. Furthermore, a coagulant may be used as necessary before the mold is immersed in the latex composition or after the mold is removed from the latex composition.

[0132] Specific examples of methods for using a coagulant include a method in which a mold before being immersed in the latex composition is immersed in a solution of the coagulant to adhere the coagulant to the mold (anodic coagulation immersion method) and a method in which a mold on which the latex composition has been deposited is immersed in a coagulant solution (Teague coagulation immersion method). Of these, the anodic coagulation immersion method is preferred in that it produces a dip-molded product with little thickness unevenness.

[0133] Specific examples of the coagulant include water-soluble polyvalent metal salts such as metal halides, such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates, such as barium nitrate, calcium nitrate, and zinc nitrate; acetates, such as barium acetate, calcium acetate, and zinc acetate; and sulfates, such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among these, calcium salts are preferred, and calcium nitrate is more preferred. These water-soluble polyvalent metal salts can be used alone or in combination of two or more.

[0134] The coagulant can usually be used as a solution of water, alcohol, or a mixture thereof, and is preferably used in the form of an aqueous solution. This aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, or a nonionic surfactant. The concentration of the coagulant varies depending on the type of water-soluble polyvalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.

[0135] After the mold is removed from the latex composition, the deposit formed on the mold is usually dried by heating under appropriately selected drying conditions.

[0136] Next, the dip-molded layer formed on the mold is crosslinked by heating. The crosslinking of the dip-molded layer can be carried out by carrying out a heat treatment at a temperature of 80 to 150°C, preferably for 10 to 130 minutes. The heating method can be an external heating method using infrared rays or heated air, or an internal heating method using high frequency waves. Of these, external heating using heated air is preferred. Before carrying out the heat treatment, the dip-molded layer may be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, excess emulsifier, coagulant, etc.). The operation of removing the water-soluble impurities may be carried out after the dip-molded layer is heat-treated, but it is preferable to carry out the operation before the heat treatment in order to more efficiently remove the water-soluble impurities.

[0137] The dip-molded layer is then removed from the dip-molding mold to obtain a dip-molded body. The method for removing the layer from the mold can be by peeling it off by hand or by using water pressure or compressed air. After the removal, the layer may be further heated at a temperature of 60 to 120°C for 10 to 120 minutes.

[0138] The film thickness of the dip-molded body is preferably 0.03 to 0.50 mm, more preferably 0.05 to 0.40 mm, and particularly preferably 0.08 to 0.30 mm.

[0139] The dip-molded article obtained by the manufacturing method of the present invention is obtained by using the above-mentioned latex composition, and is excellent in tensile strength, tensile elongation, and tear strength while suppressing the occurrence of delayed-type allergy (Type IV), and can be particularly suitably used as, for example, gloves. When the film-molded article is a glove, in order to prevent adhesion at the contact surface between the film-molded articles and to improve slippage when putting on and taking off the glove, inorganic fine particles such as talc or calcium carbonate or organic fine particles such as starch particles may be sprinkled on the glove surface, an elastomer layer containing fine particles may be formed on the glove surface, or the surface layer of the glove may be chlorinated.

[0140] In addition to the gloves described above, the dip-molded products obtained by the manufacturing method of the present invention can also be used for medical products such as baby bottle nipples, droppers, tubes, water pillows, balloon sacks, catheters, and condoms; toys such as balloons, dolls, and balls; industrial products such as pressure molding bags and gas storage bags; finger cots, etc. EXAMPLES

[0141] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, the "parts" below are based on weight unless otherwise specified. In addition, various physical properties were measured as follows.

[0142] <Solid content concentration> 2 g of the sample was weighed out (weight: X2) onto an aluminum dish (weight: X1), and dried for 2 hours in a hot air dryer at 105° C. Then, after cooling in a desiccator, the weight of the aluminum dish was measured (weight: X3), and the solid content was calculated according to the following formula. Solid content concentration (wt%)=(X3-X1)×100 / X2

[0143] <Agglomerate content> According to the above-mentioned method, the solid content concentration of the latex composition was measured, and about 100 g of the latex composition was weighed out and filtered through a 200 mesh SUS wire net with a known weight, and the aggregates on the wire net were washed with water several times to remove the latex composition. This was dried at 105°C for 60 minutes, and then its dry weight was measured, and the content of the aggregates was calculated as a percentage when the amount of the polymer component contained in the latex composition was taken as 100% by weight (unit: weight%). The lower the content of the aggregates, the more excellent the stability of the latex composition.

[0144] <Appearance of dip-molded product> The dip-molded article was visually inspected for the presence or absence of agglomerates.

[0145] <Tensile strength and tensile elongation of dip-molded body> Based on ASTM D412, the dip-molded body was punched out with a dumbbell (product name "Super Dumbbell (model: SDMK-100C)" manufactured by Dumbbell Co., Ltd.) to prepare a test piece for measuring tensile strength. The test piece was pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210" manufactured by Orientec Co., Ltd.) to measure the tensile strength (unit: MPa) just before break and the tensile elongation (unit: %) just before break.

[0146] <Tear strength of dip-molded body> Based on ASTM D624-00, the dip molded body was left in a constant temperature and humidity room at 23°C and 50% relative humidity for 24 hours or more, and then punched out with a dumbbell (product name "Die C", manufactured by Dumbbell Co., Ltd.) to prepare a test piece for measuring tear strength. The test piece was pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210", manufactured by A&D Co., Ltd.) to measure the tear strength (unit: N / mm).

[0147] <Example 1> (Production of synthetic polyisoprene (A-1) latex) 900 parts of n-hexane and 100 parts of isoprene were charged into a dried autoclave equipped with a stirrer and substituted with nitrogen. The temperature inside the autoclave was set to 60°C, and 0.05 parts of n-hexane solution containing 15% by weight of n-butyllithium as a catalyst solution was added while stirring, and the mixture was reacted for 1 hour to obtain a reaction liquid. The polymerization reaction rate was 99%. Methanol was added to the obtained reaction liquid as a polymerization terminator to terminate the reaction, thereby obtaining an n-hexane solution (a-1) (solid concentration 10% by weight) of synthetic polyisoprene with a weight average molecular weight (Mw) of 1,840,000.

[0148] On the other hand, potassium rosinate was added to water and dissolved by raising the temperature to 60° C. to prepare an aqueous emulsifier solution (b-1) with a concentration of 1.5% by weight.

[0149] Next, the synthetic polyisoprene n-hexane solution (a-1) obtained above and the emulsifier aqueous solution (b-1) were mixed using a mixer (product name "Multi Line Mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the potassium rosinate in the emulsifier aqueous solution (b-1) was 10 parts per 100 parts of synthetic polyisoprene in the synthetic polyisoprene n-hexane solution (a-1), and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.) to obtain an emulsified dispersion (c-1). At this time, the total feed flow rate of the synthetic polyisoprene n-hexane solution (a-1) and the emulsifier aqueous solution (b-1) was 2,000 kg / hr, the temperature was 60 ° C, and the back pressure (gauge pressure) was 0.5 MPa.

[0150] Next, the obtained emulsion dispersion (c-1) was heated to 80°C under reduced pressure of -0.01 to -0.09 MPa (gauge pressure), and n-hexane was distilled off to obtain an aqueous dispersion of synthetic polyisoprene (d-1). At that time, an antifoaming agent (product name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while being sprayed so that the amount was 300 ppm by weight relative to the synthetic polyisoprene in the emulsion dispersion (c-1). When distilling off n-hexane, the emulsion dispersion (c-1) was adjusted to 70% by volume or less of the tank volume, and stirring was performed slowly at 60 rpm using a three-stage inclined paddle impeller as the stirring impeller.

[0151] After completion of distillation of n-hexane, the obtained aqueous dispersion of synthetic polyisoprene (d-1) was concentrated by centrifuging at 8,000 to 9,000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to obtain a latex of synthetic polyisoprene (A-1) having a solid content concentration of 60% by weight as a light liquid. The conditions of the centrifugation were as follows: the solid content concentration of the aqueous dispersion (d-1) before centrifugation was 8% by weight, the flow rate during continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa. The obtained latex of synthetic polyisoprene (A-1) had 1 part of potassium rosinate remaining per 100 parts of synthetic polyisoprene (A-1) in the latex of synthetic polyisoprene (A-1). The synthetic polyisoprene (A-1) did not substantially contain a carboxyl group.

[0152] (Preparation of Latex Composition) While stirring the latex of synthetic polyisoprene (A-1) obtained above, β-naphthalenesulfonic acid formalin condensate sodium salt (NASF, product name "Demol T-45", manufactured by Kao Corporation) was added as a strong acid salt surfactant so that the blending amount was 1.0 part in terms of solid content per 100 parts of synthetic polyisoprene (A-1) in the latex of synthetic polyisoprene (A-1). While stirring the resulting mixture, 2.5 parts of zinc diisopropylxanthate as a xanthogen compound, 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of an antioxidant (product name "Wingstay L", manufactured by Goodyear Chemical Industries) were added as solid content equivalents to 100 parts of synthetic polyisoprene (A-1) in the mixture, and then an aqueous potassium hydroxide solution (concentration: 5.0% by weight) was added to obtain a latex composition whose pH was adjusted to 12.5 (the pH of the latex composition before aging was adjusted to 12.5).

[0153] (Aging of latex composition) The obtained latex composition was aged for 48 hours in a thermostatic water bath adjusted to 30° C. An aqueous potassium hydroxide solution (concentration: 5.0% by weight) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 12.1. After 12 hours from the start of aging, the pH of the latex composition before the addition of the aqueous potassium hydroxide solution was 11.6, and the pH of the latex composition after 48 hours of aging was 11.8.

[0154] The pH of the latex composition during aging gradually decreased from the start of aging until 12 hours later, and reached the pH of the latex composition after 12 hours of aging (the same applies to each of the Examples and Comparative Examples described below). That is, the pH of the latex composition during aging was continuously maintained at a pH equal to or higher than the pH of the latex composition after 12 hours of aging. For example, in Example 1, the pH of the latex composition at the start of aging was 12.6, and the pH gradually decreased with aging, and the pH of the latex composition after 12 hours from the start of aging was 11.6. That is, in Example 1, the pH of the latex composition was continuously maintained at 11.6 or higher until 12 hours from the start of aging.

[0155] (Production of dip-molded body) A commercially available ceramic hand mold (manufactured by Shinko Co., Ltd.) was washed and preheated in an oven at 70°C, then immersed in an aqueous coagulant solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "Emulgen 109P", manufactured by Kao Co., Ltd.) for 5 seconds and removed from the aqueous coagulant solution. The hand mold was then dried in an oven at 70°C for 30 minutes or more to allow the coagulant to adhere to the hand mold, thereby coating the hand mold with the coagulant.

[0156] The hand mold covered with the coagulant was then removed from the oven and immersed in the latex composition obtained above after aging for 48 hours for 10 seconds. The hand mold was then air-dried at room temperature for 10 minutes, and then immersed in 60°C warm water for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the hand mold. The dip-molded layer formed on the hand mold was then crosslinked by heating in an oven at a temperature of 130°C for 30 minutes, cooled to room temperature, and talc was sprayed on it before peeling it off from the hand mold to obtain a dip-molded body (rubber glove). The obtained dip-molded body (rubber glove) was evaluated for coagulation content, appearance, tensile strength, tensile elongation, and tear strength according to the above-mentioned method. The results are shown in Table 1. The appearance of the obtained dip-molded body (rubber glove) was good and had no particular problems (the same applies to each example described below).

[0157] <Example 2> A latex composition before aging with a pH of 11.1 was obtained in the same manner as in Example 1, except that the amount of pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In Example 2, a potassium hydroxide aqueous solution (concentration: 5.0% by weight) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 11.0. In addition, 12 hours after the start of aging, the pH of the latex composition before the addition of the potassium hydroxide aqueous solution was 10.4, and the pH of the latex composition after 48 hours of aging was 10.8. A dip-molded product (rubber glove) was produced using the latex composition after 48 hours of aging in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.

[0158] <Example 3> A latex composition before aging with a pH of 11.1 was obtained in the same manner as in Example 1, except that the amount of pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In Example 3, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. The pH of the latex composition 12 hours after the start of aging was 10.4, and the pH of the latex composition after aging was 10.1. A dip-molded product (rubber glove) was produced using the latex composition after aging for 48 hours in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.

[0159] <Example 4> A latex composition before aging with a pH of 11.1 was obtained in the same manner as in Example 1, except that β-naphthalenesulfonic acid formalin condensate sodium salt (NASF) was not added to the latex composition before aging and the amount of pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In Example 4, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. The pH of the latex composition 12 hours after the start of aging was 10.5, and the pH of the latex composition after aging was 10.2. A dip-molded product (rubber glove) was produced in the same manner as in Example 1 using the latex composition after aging for 48 hours, and was evaluated in the same manner. The results are shown in Table 1.

[0160] <Example 5> A latex composition before aging was obtained in the same manner as in Example 4. The pH of the obtained latex composition before aging was 11.1. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1, except that the temperature of the thermostatic water bath was adjusted to 25°C. In Example 5, a pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. The pH of the latex composition 12 hours after the start of aging was 10.3, and the pH of the latex composition after aging was 10.1. A dip-molded product (rubber glove) was produced using the latex composition after aging for 48 hours in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.

[0161] <Comparative Example 1> A latex composition before aging with a pH of 9.5 was obtained in the same manner as in Example 1, except that the amount of pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In Comparative Example 1, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. The pH of the latex composition 12 hours after the start of aging was 8.5, and the pH of the latex composition after aging was 8.2. A dip-molded product (rubber glove) was produced using the latex composition after aging for 48 hours in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1. The appearance of the dip-molded product (rubber glove) obtained in Comparative Example 1 was such that it was visually confirmed that several aggregates were attached.

[0162] <Comparative Example 2> A latex composition before aging with a pH of 9.5 was obtained in the same manner as in Example 1, except that β-naphthalenesulfonic acid formalin condensate sodium salt (NASF) was not added to the latex composition before aging and the amount of pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. The obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In Comparative Example 2, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. The pH of the latex composition 12 hours after the start of aging was 8.3, and the pH of the latex composition after aging was 8.1. The latex composition obtained in Comparative Example 1 had significant generation of aggregates (amount of aggregates: 52.5% by weight), and a dip-molded product could not be produced. The results are shown in Table 1.

[0163] [Table 1]

[0164] As shown in Table 1, the latex composition obtained by the manufacturing method in which a sulfur-based vulcanizing agent and a xanthogen compound are added to the prepared conjugated diene polymer latex to obtain a latex composition before aging, and then the latex composition before aging is aged to have a pH of 9 or more 12 hours after the start of aging, is excellent in stability and can suppress the generation of aggregates, and further, when the dip-molded product is obtained, the obtained dip-molded product is excellent in tensile strength, tensile elongation, and tear strength (Examples 1 to 5). In addition, since the obtained latex composition does not contain a vulcanization accelerator that causes the symptoms of delayed-type allergy (Type IV), it is considered that the obtained dip-molded product can prevent the occurrence of delayed-type allergy (Type IV) when it is dip-molded. On the other hand, when the pH of the latex composition 12 hours after the start of aging is less than 9, the resulting latex composition is inferior in stability and generates a large amount of aggregates, making it impossible to produce a dip-molded article (Comparative Example 2). Even if a dip-molded article can be produced, the resulting dip-molded article has aggregates attached thereto and is inferior in tensile strength and tear strength (Comparative Example 1).

Claims

1. A preparation step of preparing a conjugated diene polymer latex; a preparation step of adding a sulfur-based vulcanizing agent and a xanthogen compound to the conjugated diene polymer latex to obtain a pre-ripening latex composition; and an aging step of preparing the pre-aged latex composition and then storing the prepared pre-aged latex composition at a temperature of 5 to 60° C. for 12 hours to 14 days to age the composition, the conjugated diene polymer latex is a latex of a conjugated diene polymer having no carboxyl group, The method for producing a latex composition, wherein in the aging step, the pH of the latex composition 12 hours after the start of aging is set to 9 or more.

2. 2. The method for producing a latex composition according to claim 1, wherein in the preparation step, the pH of the latex composition before aging is adjusted to 11 or more.

3. 3. The method for producing a latex composition according to claim 1, wherein a pH adjuster is added to the latex composition during maturation in the maturation step.

4. 4. The method for producing a latex composition according to claim 3, wherein the pH adjuster comprises at least one selected from the group consisting of an alkali metal hydroxide, ammonia, and an organic amine compound.

5. The method for producing a latex composition according to any one of claims 1 to 4, wherein the amount of the sulfur-based vulcanizing agent is 0.01 to 3 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.

6. The method for producing a latex composition according to any one of claims 1 to 5, wherein the amount of the xanthogen compound used is 0.01 to 10 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.

7. 7. The method for producing a latex composition according to claim 1, wherein in the preparation step, a strong acid salt surfactant is further added to the conjugated diene polymer latex.

8. The method for producing a latex composition according to any one of claims 1 to 7, wherein the conjugated diene polymer latex is a synthetic polyisoprene latex, a styrene-isoprene-styrene block copolymer latex, or a deproteinized natural rubber latex.

9. A method for producing a dip-molded product, comprising a step of dip-molding a latex composition obtained by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Curable polymer latex composition for making rubber products

    JP2020503401A

  • Latex for dip molding use, composition for dip molding use, and dip-molded article

    WO2014129547A1

  • Latex composition for dip molding and dip-molded article

    WO2016104057A1

  • Dip-molded product

    WO2016104058A1

  • Latex composition

    WO2018155243A1